Kartu Jodoh Sebagai Media Peningkatan Kemampuan Mengartikan Asmaul Husna Siswa - Rasiti Rasiti; St Umrah (IAIN Sorong, 2020)
The ability to interpret the Asmaul Husna which is still low on students of SD Inpres 22 Sorong is the background of the research in this thesis. This study aims to improve the ability to interpret Asmaul Husna on Islamic Education (PAI) subjects by using Matchmaking Learning Media in class II SD Inpres 22 Sorong Regency. This study is a classroom action research (PTK), with subjects in grade II at SD Inpres 22 Sorong in the 2017/2018 school year, totaling 6 people. This research was conducted in 2 cycles, each cycle carried out in 2 meetings. Data retrieval is done by using tests and observations. The collected data were analyzed using percentage descriptive analysis. The results obtained after being given the action are (1) the average score of the ability test to interpret Asmaul Husna students in the first cycle is 76.67 and the average score in the second cycle is 86.67. It can be concluded that matchmaking card learning media can improve the ability to interpret Asmaul Husna in Islamic Education (PAI) lessons in class II SD Inpres 22 Sorong.